2013
DOI: 10.1111/appy.12072
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing and internalizing syndromes in relation to school truancy among adolescents in high‐risk urban schools

Abstract: Introduction: To examine the relationship between externalizing/ internalizing syndromes and school truancy among Form Four (10th grade) students attending "high-risk" schools in Kuala Lumpur. Methods: This is a cross-sectional study conducted upon 16-year-old adolescents attending three high-risk schools in Kuala Lumpur. A total of 373 students completed self-administered questionnaires on the sociodemographic variables and externalizing/internalizing syndromes. The number of truant-days per student during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
2
15
0
1
Order By: Relevance
“…We undertook a secondary analysis of the 2004 British Child and Adolescent Mental Health Survey (BCAMHS) [21], which is a large, nationally-representative dataset that spans from 5 to 16 years. Although previous research has suggested that behavioural disorders are also related to school absence, particularly unauthorised absence or truancy [28,29], the present study focuses on anxiety and depression because these disorders are so frequently unrecognised by adults around the child, particularly in education settings [30]. The BCAMHS benefits from having diagnostic measures of emotional disorder in addition to measures of emotional symptoms and school absence.…”
Section: Introductionmentioning
confidence: 99%
“…We undertook a secondary analysis of the 2004 British Child and Adolescent Mental Health Survey (BCAMHS) [21], which is a large, nationally-representative dataset that spans from 5 to 16 years. Although previous research has suggested that behavioural disorders are also related to school absence, particularly unauthorised absence or truancy [28,29], the present study focuses on anxiety and depression because these disorders are so frequently unrecognised by adults around the child, particularly in education settings [30]. The BCAMHS benefits from having diagnostic measures of emotional disorder in addition to measures of emotional symptoms and school absence.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, [24] reported that there is significant difference of perception on causes of truancy among male and female adolescent. However, we also found few studies stated that gender difference did not influence truant behaviour and the prevalence of truancy among the gender show no significant different [18] [25] and [26].…”
Section: Discussionmentioning
confidence: 73%
“…Details on other research aimed at studying the nature, causes, distribution and management of externalizing behavior in children and adolescents can be found in [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. Sample (field) survey was used to obtain the data, similar researches that used field survey to obtain their data can also be found in [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%